Pharmacokinetic Profile of Liposome-Encapsulated Ropivacaine after Maxillary Infiltration Anaesthesia - Franz-Montan, Michelle; Bergamaschi, Cristiane de Cassia; de Paula, Eneida; Groppo, Francisco C.; Ranali, Jose; Fraceto, Leonardo Fernandes [UNESP]; Volpato, Maria C. (Soc Brasileira Quimica, 2010)
The aim of this study was to determine the pharmacokinetic parameters of liposomal ropivacaine after dental anesthesia in 14 healthy volunteers. In this randomized, double-blind and crossover study, the volunteers received maxillary infiltration of liposome-encapsulated 0.5% ropivacaine and, 0.5% ropivacaine with 1:200,000 epinephrine in two different sessions. Blood samples were collected before and after (from 15 to 1440 min) the administration of either ropivacaine formulation. HPLC with UV detection was used to quantify plasma ropivacaine concentrations. The pharmacokinetic parameters AUC(0-24) (area under the plasma concentration x time curve from baseline to 24 h), AUC(0-infinity) (area under the plasma concentration-time curve from baseline to infinity), C-max (maximum drug concentration), CL (renal clearance), T-max (maximum drug concentration time), t(1/2) (elimination half-life) and Vd (volume of distribution) were analyzed using the Wilcoxon signed-rank test. No differences (p > 0.05) were observed between both formulations for any of the pharmacokinetic parameters evaluated and plasma ropivacaine concentrations, considering each period of time. Both formulations showed similar pharmacokinetic profiles, indicating that the liposomal formulation could be a safer option for use of this local anesthetic, due to the absence of a vasoconstrictor.
Keywords: ropivacaine; local anesthesia; dentistry; liposome; pharmacokinetic